Exploring the Bidirectional Associations Between Short or Long Sleep Duration and Lower Cognitive Function: A 7-Year Cohort Study in China - Hua, Jianian; Zhuang, Sheng; Shen, Yueping; Tang, Xiang; Sun, Hongpeng; Fang, Qi (Frontiers in Aging Neuroscience, 2021)
Background: Sleep duration is linked to cognitive function, but whether short or prolonged sleep duration results from impaired cognition or vice versa has been controversial in previous studies. We aimed to investigate the bidirectional association between sleep duration and cognitive function in older Chinese participants. Methods: Data were obtained from a nationally representative study conducted in China. A total of 7984 participants aged 45 years or older were assessed at baseline between June 2011 and March 2012 (Wave 1), 2013 (Wave 2), 2015 (Wave 3), and 2018 (Wave 4). Nocturnal sleep duration was evaluated using interviews. Cognitive function was examined via assessments of global cognition, including episodic memory, visuospatial construction, calculation, orientation and attention capacity. Latent growth models and cross-lagged models were used to assess the bidirectional association between sleep duration and cognitive function. Results: Among the 7,984 participants who were followed in the four waves of the study, the baseline mean (SD) age was 64.7 (8.4) years, 3862 (48.4%) were male, and 6453 (80.7%) lived in rural areas. Latent growth models showed that both sleep duration and global cognition worsened over time. Cross-lagged models indicated that short or long sleep duration in the previous wave was associated with lower global cognition in the subsequent wave (standardized β = −0.066; 95% CI: −0.073, −0.059; P < 0.001; Wave 1 to 2) and that lower global cognition in the previous wave was associated with short or long sleep duration in the subsequent wave (standardized β = −0.106; 95% CI: −0.116, −0.096; P < 0.001; Wave 1 to 2). Conclusion: There was a bidirectional association between sleep duration and cognitive function, with lower cognitive function having a stronger association with long or short sleep duration than the reverse relationship. Global cognition was likely the major driver in these reciprocal associations.